Золотой теленок: роман / И. Ильф, Е. Петров - Ильф Илья Арнольдович (Советская Россия, 1991)
Экземпляры: ф.5 (1991) / Инвентарный номер: 33332 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: И 48 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44